The International Conference on Children, Repression and the Law in Apartheid South Africa - Dawes, Andrew (PINS-Psychology in Society, 2025)
I was privileged to be invited by the Law Faculty of the University of Zimbabwe to present an address at the Harare gathering. Together with Don Foster of my department at U.C.T., who also presented a keynote address, I represented the Organisation for Appropriate Social Services in South Africa (OASSSA). The Harare conference had many facets, and it is not easy to convey the truly momentous nature of this occasion. I shall nonetheless attempt to do so, recognising that it is impossible to do the experience justice.